Disruptions to the cerebellar GABAergic system in juvenile guinea pigs following preterm birth. Issue 65 (April 2018) - Shaw, Julia C.; Palliser, Hannah K.; Dyson, Rebecca M.; Berry, Mary J.; Hirst, Jonathan J.
Highlights: Children born preterm are at risk of cognitive problems and behavioural disorders. Myelination and GABAergic neurons are disrupted in juvenile preterm guinea pigs. Premature loss of neurosteroids post birth may be involved in these disruptions. Abstract: Background: Children that are born preterm are at an increased risk of developing cognitive problems and behavioural disorders, such as attention deficit hyperactivity disorder (ADHD). There is increasing interest in the role of the cerebellum in these processes and the potential involvement of GABAergic pathways in neurodevelopmental disorders. We propose that preterm birth, and the associated loss of the trophic intrauterine environment, alters the development of the cerebellum, contributing to ongoing neurobehavioral disorders. Methods: Guinea pigs were delivered preterm (GA62) or spontaneously at term (GA69), and tissues collected at corrected postnatal day (PND) 28. Neurodevelopmental and GABAergic markers myelin basic protein (MBP), neuronal nuclei (NeuN), calbindin (Purkinje cells), and GAD67 (GABA synthesis enzyme) were analysed in cerebellar lobules IX and X by immunohistochemistry. Protein expression of GAD67 and GAT1 (GABA transporter enzyme) were quantified by western blot, whilst neurosteroid-sensitive GABAA receptor subunits were measured by RT-PCR. Results: MBP immunostaining was increased in lobule IX of preterm males, and reduced in lobule X of preterm females when compared to their term counterparts. GAD67 staining was decreased in lobule IX and X of the preterm males, but only in lobule X of the preterm females compared to term cohorts for each sex. Internal granule cell layer width of lobule X was decreased in preterm cohorts of both sexes compared to terms. There were no differences between gestational age groups for NeuN staining, GAD67 and GAT1 protein expression as measured by western blotting, or GABAA receptor subunits as measured by RT-PCR between preterm and term for either sex. Conclusions: The present findings suggest that components of the cerebellar GABAergic system of the ex-preterm cerebellum are disrupted. The higher expression of myelin in the preterm males may be due to a deficit in axonal pruning, whereas females have a deficit in myelination at 28 corrected days of age. Together these ongoing alterations may contribute to the neurodevelopmental and behavioural disorders observed in those born preterm.